The best of I-Witness, volume 3 - Taruc, Jose Reyes III; David, Kara S.; Aguinaldo, Sandra S.; Severino, Horacio (GMA Network, 2006)
Collection of best episodes of I witness, a documentary television show in the Philippines by GMA Network. This volume presents: the daily life of poor Filipinos experiencing hunger and poverty, recruiting women in the barrios to work in the province night clubs, children catching squid from Masbate to earn money and the construction of the Manila Film Center and the people who died building it.